2021
DOI: 10.1371/journal.pone.0251711
|View full text |Cite
|
Sign up to set email alerts
|

The impact of urinary incontinence on falls: A systematic review and meta-analysis

Abstract: Objective Previous studies on the association between urinary incontinence (UI) and falls have reported conflicting results. We, therefore, aimed to evaluate and clarify this association through a systematic review and meta-analysis of relevant studies. Methods We performed a literature search for relevant studies in databases including PubMed and EMBASE from inception up to December 13, 2020, using several search terms related to UI and falls. Based on the data reported in these studies, we calculated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 55 publications
4
42
0
7
Order By: Relevance
“…Second, we excluded many participants due to missing data and conducted our research as a cross-sectional study, resulting in limited power. Several studies have found a relationship between nocturia and hip fractures in older people, and nocturia among these older populations is likely to cause hip fractures and death [ 25 , 26 ]. However, we did not have data to determine the association between nocturia and the risk of hip fractures and subsequent mortality risk in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we excluded many participants due to missing data and conducted our research as a cross-sectional study, resulting in limited power. Several studies have found a relationship between nocturia and hip fractures in older people, and nocturia among these older populations is likely to cause hip fractures and death [ 25 , 26 ]. However, we did not have data to determine the association between nocturia and the risk of hip fractures and subsequent mortality risk in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Im Zusammenspiel von Multimorbidität, Umgebungsfaktoren und weiteren Kontextfaktoren, die sich gegenseitig beeinflussen können, muss dies bei der Diagnostik und der Therapie berücksichtigt werden. Inkontinenz selbst führt zu vermehrter Immobilität, damit zu Stürzen bei Älteren und zu seelischen Beeinträchtigungen [8]. Dies kann wiederum Inkontinenz befördern.…”
Section: Harninkontinenz Als Symptom Und Geriatrisches Syndromunclassified
“…UI is the objectively demonstrable involuntary loss of urine that increases the subject's frailty, their physical inactivity, their risk of falls, and their immobility; decreases their functional independence; and has negative physiological effects due to hygienic problems [4,[9][10][11][12][13][14][15][16][17]. Also, UI greatly impacts on psychological health, severely affects normal social interaction and leisure activities, increases the risk of self-imposed isolation and cognitive impairment, and decreases satisfaction and quality of life (QoL) [10,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%